Clonidine versus fentanyl as adjuvant to 0.75% ropivacaine for epidural anesthesia for lower limb surgeries: a comparative evaluation - Agarwal, Salony; Gupta, Kumkum; Gupta, Prashant K.; Bansal, Manoranjan; Sharma, Raaghav; Buchh, Aqsa (International Journal of Research in Medical Sciences, 2017)
Background: Epidural adjuvants to local anaesthetic are used to enhance the quality and duration of surgical anaesthesia. The present study was aimed to compare the clinical efficacy of clonidine with fentanyl as adjuvant to epidural ropivacaine for block characteristics and hemodynamic changes during lower limb surgeries. Methods: Sixty adult consenting patients of both gender of ASA physical status I and II scheduled for lower limb surgeries under epidural anaesthesia, were randomized into two groups of 30 patients each to receive either 15 ml of 0.75% ropivacaine with 1 ml of clonidine, 50 µg (Group RC) or with 1 ml of fentanyl 50 µg (Group RF). All patients were assessed for onset and duration of sensory and motor blockade and time to first rescue analgesia as primary end points. The hemodynamic variations, sedation, pruritus, respiratory depression or any other adverse events were recorded as secondary end points. Results: Onset of sensory block to T10 was comparable between the groups. Time to achieve maximum sensory level at T6-7 and maximum motor block was faster when fentanyl was used as compared to clonidine with statistically significant difference between the group (p<0.05). Duration of sensory analgesia was enhanced with epidural clonidine, delaying the need for rescue analgesia. In clonidine group, side effects of sedation, bradycardia and hypotension were also observed. Only 5 patients of fentanyl group suffered from pruritus. Conclusions: Clonidine was more effective than fentanyl as epidural adjuvant to 0.75% ropivacaine for prolonging the duration of analgesia with fewer manageable side effects.